2015
DOI: 10.1038/srep15935
|View full text |Cite
|
Sign up to set email alerts
|

Optical fiber tip templating using direct focused ion beam milling

Abstract: We report on a method for integrating sub-wavelength resonant structures on top of optical fiber tip. Our fabrication technique is based on direct milling of the glass on the fiber facet by means of focused ion beam. The patterned fiber tip acts as a structured template for successive depositions of any responsive or functional overlay. The proposed method is validated by depositing on the patterned fiber a high refractive index material layer, to obtain a ‘double-layer’ photonic crystal slab supporting guided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Figure e shows the 1DDG profile along a scan line parallel to the periodicity axis and some results of the measurements (see the Supporting Information for AFM images of the pattern). As expected, the profile is pseudo‐trapezoidal. This effect is inherent of the FIB patterning process, which leads to an array of strips nonuniform along their depth, that is, wider than the nominal width Λ (1 − DC) = 770 nm on the top, and narrower on the bottom.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Figure e shows the 1DDG profile along a scan line parallel to the periodicity axis and some results of the measurements (see the Supporting Information for AFM images of the pattern). As expected, the profile is pseudo‐trapezoidal. This effect is inherent of the FIB patterning process, which leads to an array of strips nonuniform along their depth, that is, wider than the nominal width Λ (1 − DC) = 770 nm on the top, and narrower on the bottom.…”
Section: Resultssupporting
confidence: 81%
“…, where a gradual reduction of the active region of a metallo‐dielectric plasmonic nanostructure from the entire cladding area down to a square area of 20 µm × 20 µm did not yield substantial variations in the retrieved spectral features, revealing a good robustness of the structure against finite‐size effects. Nevertheless, “edge” effects are known to strongly limit the outcoupling process in dielectric structures supporting high‐ Q propagating modes, with detrimental influence on the resonance visibility and bandwidth, as discussed and observed for both planar and fiber‐tip photonic resonators. In our case, if the BSW is not efficiently enclosed within the patterned area on the fiber tip, unavoidable losses are expected, due to both scattering at the discontinuity and coupling to BSWs sustained by the planar 1DPC surface outside the grating boundary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Micco et al. proposed a technique for templating the optical fiber tip . The process is based on a direct writing process followed by a high RI (nSiOx) overlay deposition, giving rise to a ‘double‐layer’ PC slab supporting guided resonances.…”
Section: Lab On Tipmentioning
confidence: 99%
“…The 1DPC is terminated with a SiO layer, and the external medium is air ( 1 ext n = ). As customary in lab-on-fiber scenarios [28,29,[33][34][35][36], in order to guarantee the computational affordability of our numerical study, we approximate the impinging fiber mode with a normally-incident plane wave, thereby neglecting the illumination tapering and polarization non-uniformity. It is worth emphasizing that previous experimental validations in other lab-on-fiber configurations have indicated that this approximation typically provides acceptable accuracy in the prediction of the optical response and sensitivity [28,[33][34][35][36].…”
Section: Geometry and Generalitiesmentioning
confidence: 99%